Malaysian license plate recognition using sobel algorithm / Mohamad Izzuddin Sofian - Sofian, Mohamad Izzuddin (2013)
These different types of license plate being used, each country needs different requirement automatic license plate recognition. In this paper license plate recognition using sobel algorithm is proposed for Malaysian vehicle with standard format license plate based on image processing. It also focus on street line plate number not in double line plate number. After snapshot of car were run on the system, it will transform or invert the images into gray scale image. Typically sobel is used to find the approximate absolute gradient magnitude at each point in an input gray scale his image. The experiment had been done in order to measure the percentage of accuracy of this system. From this experiment, the prototype system produces 40% accuracy rate of identifying correct license plate.